Analisis Arus Kas dan Sistem Pengendalian Internal Arus Kas PT. Yuli Madya Barometer Palembang - Hayati, Sukma; Valianti, Reva Maria; Oktariansyah, Oktariansyah (Jurnal Media Akuntansi (Mediasi), 2025)
ABSTRACT The purpose of this study is description, qualitative analysis, methods used, qualitative description, a set of actions or processes to filter data and information that are related to a problem in a given situation. Aspect or field of study. The results showed that the company's internal financial control system was fully structured and involved other departments, especially the marketing and finance departments. In the elements of the confirmation system and accounting procedures, the cash flow management system reflected all activities related to payments and recipients, as well as the preparation of invoices according to the procedure, but cash receipts were not reflected in the credit of receivables. And considering the best practice elements of your company, it makes sense to register money based on the documents entered and ensure that all of your company's money is covered. However, the internal control system of remittances already deals with accounting and financial functions, separating other departments. Confirmation systems and accounting procedures dealt with cash payments and confirmations, as well as posting, posting and closing payment books. However, it is not good practice for tellers to regularly compare bank statements and accounting information to reconcile business and cash with the bank. There are internal controls that have not yet been fully implemented in the company, so follow the relevant policies and procedures. In this case, this means that the company must make constant adjustments to better meet expectations. Keywords: Internal Cash Flow Management System, Organizational Structure, Certification System, Registration Procedure, Best Practices. ABSTRAK Tujuan penelitian ini adalah deskripsi, analisis kualitatif, metode yang digunakan, deskripsi kualitatif, serangkaian kegiatan atau proses untuk menyaring data dan informasi yang berkaitan dengan situasi tertentu. Aspek atau bidang studi. Hasilnya menunjukkan bahwa sistem pengelolaan arus kas internal perusahaan sudah terstruktur sepenuhnya dan mencakup departemen lain terutama pemasaran dan keuangan. Mengenai sistem koordinasi dan prosedur akuntansi, dalam sistem pengelolaan arus kas, seluruh aktivitas dan tagihan yang berhubungan dengan kredit dan piutang dicatat sesuai urutan pembuatan faktur, namun penerimaan kas tidak dicatat sebagai piutang kredit. Dan dengan mempertimbangkan elemen praktik terbaik perusahaan Anda, adalah tepat untuk mendaftarkan uang berdasarkan dokumen yang dimasukkan dan memastikan bahwa semua keuangan perusahaan Anda tercakup. Namun, sistem pengendalian pengiriman uang internal menangani fungsi akuntansi dan keuangan, memisahkan departemen lain. Sistem konfirmasi dan prosedur akuntansi berhubungan dengan pembayaran tunai dan rekonsiliasi, serta pencatatan, pencatatan dan penutupan buku pembayaran. Namun, bukanlah praktik yang baik bagi bendahara untuk secara rutin membandingkan laporan bank dan informasi akuntansi untuk merekonsiliasi kas perusahaan dengan bank. Terdapat pengendalian internal yang belum diterapkan sepenuhnya di dalam perusahaan, sehingga ikuti kebijakan dan prosedur yang relevan. Dalam hal ini berarti perusahaan harus senantiasa melakukan perubahan agar lebih memenuhi harapan. Kata kunci: Pengendalian Internal Penerimaan dan Pengeluaran, Struktur Organisasi, Sistem Verifikasi, Prosedur Pencatatan, Best Practice.